Microcystic Variant of an Intraosseous Meningioma in the Frontal Area: A Case Report - Jan Bujok; Marek Bienioszek (Case Reports in Neurological Medicine)
Meningiomas located inside the bone of the calvaria belong to the group of rare types of tumours. The microcystic variant is the least common in this area. Due to their similarity to other tumours in this area, the imaging test of those tumours may constitute the source of an improper preoperative diagnosis. According to the records of the Department of Neurosurgery in Bielsko-Biała, 133 patients diagnosed with an intracranial meningioma confirmed by a histopathological test were operated in the last 10 years (2004–2014). In the histopathological test, three patients were diagnosed with the microcystic variant, which constitutes 2.25% of the cases. Only one variant of microcystic meningioma was located inside the bone, which constitutes 0.75% of all the meningiomas operated.